Phoca vitulina_C2_150% - Lauridsen, Henrik; Hansen, Kasper; Nørgård, Mathias Ø.; Wang, Tobias; Pedersen, Michael (Dryad Digital Repository, 2016)
Ready to 3D print STL file of Phoca vitulina C2 (axis).